2017
DOI: 10.1111/cbdd.12993
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic potential of chemically modified siRNA: Recent trends

Abstract: Small Interfering RNAs (siRNAs) are one of the valuable tools to investigate the functions of genes, and are also used for gene silencing. It has a wide scope in drug discovery through in vivo target validation. siRNA therapeutics are not optimal drug-like molecules due to poor bioavailability, immunogenic and off-target effects. In order to overcome the challenges associated with siRNA therapeutics, identification of appropriate chemical modifications that improves the stability, specificity and potency of si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
68
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(74 citation statements)
references
References 62 publications
1
68
0
2
Order By: Relevance
“…The exact mechanisms of how amphiphilic modification leads to subcellular organelle accumulation remain poorly established, but it is believed that the overall physicochemical properties and ligand–receptor interactions govern the intracellular sorting and trafficking pathways . For example, amphiphilic modification is an effective way for cytosolic targeting of small interfering RNAs (siRNA) . Lipophilic ligands modified siRNA associate with high density lipoproteins and cross the membrane directly into cytoplasm via non‐endocytotic pathway mediated by the scavenger receptor BI .…”
Section: The Design Principles Of Self‐delivery Amphiphilic Drugsmentioning
confidence: 99%
See 1 more Smart Citation
“…The exact mechanisms of how amphiphilic modification leads to subcellular organelle accumulation remain poorly established, but it is believed that the overall physicochemical properties and ligand–receptor interactions govern the intracellular sorting and trafficking pathways . For example, amphiphilic modification is an effective way for cytosolic targeting of small interfering RNAs (siRNA) . Lipophilic ligands modified siRNA associate with high density lipoproteins and cross the membrane directly into cytoplasm via non‐endocytotic pathway mediated by the scavenger receptor BI .…”
Section: The Design Principles Of Self‐delivery Amphiphilic Drugsmentioning
confidence: 99%
“…Lipophilic ligands modified siRNA associate with high density lipoproteins and cross the membrane directly into cytoplasm via non‐endocytotic pathway mediated by the scavenger receptor BI . A wide range of lipophilic moieties including cholesterol, fatty acids, and steroids were used for siRNA conjugation and some of them have reached clinical stage . Amphiphilic modification has also been utilized for the endosomal entrapment in drug delivery.…”
Section: The Design Principles Of Self‐delivery Amphiphilic Drugsmentioning
confidence: 99%
“…Short interfering RNAs are a class of biological molecules that have the potential to be next generation therapeutics . However, due to issues related to delivery, stability, and off‐target effects, siRNAs still require some forms of chemical modification to make them effective pharmaceutical candidates …”
Section: Figurementioning
confidence: 99%
“…Free siRNA including VEGF siRNA and random siRNA showed little biological activity due to their instability and fast degradation. 29 In order to understand the potency of PLCP in tumor inhibition application, VEGF siRNA was delivered into the tumor xenografts. The results demonstrated that PLCP led to a significantly higher tumor growth inhibition than negative control saline (Figure 3), while the use of Scr siRNA showing little tumor inhibition also confirmed the sequence specificity in line with in vitro study.…”
mentioning
confidence: 99%